WEAKNESSES IN LAW ENFORCEMENT, PROCEDURAL JUSTICE AND LEGAL CHALLENGES IN DEALING WITH DEVIANT SEXUAL CONDUCT CASES IN MALAYSIA: A SYSTEMATIC LITERATURE REVIEW (SLR) - Arsad, Muhammad Ilhamuddin; Nasri, Mohd Sabree; Ibrhim, Abdul Karim; Romli, Shahrina (Jurnal ’Ulwan, 2025)
The “Spa Songsang” case, involving the release of 171 individuals after the court rejected a remand application due to procedural delay, has generated significant debate among the public, legal practitioners and Shariah scholars in Malaysia. This incident reflects deeper structural issues within the criminal justice system, particularly concerning procedural justice, evidentiary constraints and the coherence between civil law and Islamic legal principles. This study employs a Systematic Literature Review (SLR) to analyse scholarly discussions on the enforcement of laws relating to deviant sexual conduct, procedural shortcomings in criminal investigations, jurisdictional conflicts and their implications from the perspective of Maqasid al-Shariah. By reviewing academic articles, legal commentaries and Shariah-based studies, the findings reveal that enforcement failures are not primarily caused by the absence of legal provisions, but rather by weaknesses in procedural compliance, evidentiary limitations and the lack of an integrated preventive framework. The study proposes comprehensive reforms involving procedural enhancement, capacity building for enforcement agencies and a maqasid-oriented preventive approach to address social morality issues more effectively.